Selective head cooling in the acute phase of concussive injury: a neuroimaging study - Walter, Alexa E.; Bai, Xiaoxiao; Wilkes, James; Neuberger, Thomas; Sebastianelli, Wayne; Slobounov, Semyon M. (Frontiers in Neurology, 2023)
Introduction Neurovascular decoupling is a common consequence after brain injuries like sports-related concussion. Failure to appropriately match cerebral blood flow (CBF) with increases in metabolic demands of the brain can lead to alterations in neurological function and symptom presentation. Therapeutic hypothermia has been used in medicine for neuroprotection and has been shown to improve outcome. This study aimed to examine the real time effect of selective head cooling on healthy controls and concussed athletes via magnetic resonance spectroscopy (MRS) and arterial spin labeling (ASL) measures. Methods 24 participants (12 controls; 12 concussed) underwent study procedures including the Post-Concussion Symptom Severity (PCSS) Rating Form and an MRI cooling protocol (pre-cooling (T1 MPRAGE, ASL, single volume spectroscopy (SVS)); during cooling (ASL, SVS)). Results Results showed general decreases in brain temperature as a function of time for both groups. Repeated measures ANOVA showed a significant main effect of time (F = 7.94, p < 0.001) and group (F = 22.21, p < 0.001) on temperature, but no significant interaction of group and time (F = 1.36, p = 0.237). CBF assessed via ASL was non-significantly lower in concussed individuals at pre-cooling and generalized linear mixed model analyses demonstrated a significant main effect of time for the occipital left ROI (F = 11.29, p = 0.002) and occipital right ROI (F = 13.39, p = 0.001). There was no relationship between any MRI metric and PCSS symptom burden. Discussion These findings suggest the feasibility of MRS thermometry to monitor alterations of brain temperature in concussed athletes and that metabolic responses in response to cooling after concussion may differ from controls.